2017
DOI: 10.1051/shsconf/20173407005
|View full text |Cite
|
Sign up to set email alerts
|

Fair Value Accounting and the Cost of Equity Capital: The Moderating Effect of Risk Disclosure

Abstract: Abstract. Evidence thus far suggests fair value accounting poses risk and affects firms' returns in some ways. This research, on a sample of Asian banks, improves the understanding of the information risk effect of fair value accounting by examining the moderating role of risk disclosure in the relationship between fair value accounting and the cost of equity capital. The results from a generalised method of moments on dynamic panel data analysis, show that risk disclosure mitigates the asymmetric information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Particularly, better boards promote the disclosure of more information on risks. In line with the recent literature (Dignah et al, 2017), RDs are documented as having an important impact on the mitigation of information asymmetries, thereby leading to a reduction in the CC. Indeed, hypothesis H2 is supported.…”
Section: Data Analysis and Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Particularly, better boards promote the disclosure of more information on risks. In line with the recent literature (Dignah et al, 2017), RDs are documented as having an important impact on the mitigation of information asymmetries, thereby leading to a reduction in the CC. Indeed, hypothesis H2 is supported.…”
Section: Data Analysis and Resultssupporting
confidence: 69%
“…Furthermore, a large stream of research suggests that a decrease in information asymmetries can lead to a reduction in the CC (Botosan, 2006;Diamond and Verrecchia, 1991;Lamber et al, 2012). Although the effect on information disclosure may depend on the context and the type of information (Dutta and Nezlobin, 2017;Gao, 2010;Orens et al, 2009), the previous literature suggests that RDs have a strong ability to reduce the CC (Dignah et al, 2017). Specifically, information on risks allows outsiders to better assess a company's future economic performance and reduce the information gap between managers and outsiders (Dobler, 2008;Linsley and Shrives, 2006).…”
Section: The Mediated Effect Of Rdsmentioning
confidence: 99%
“…It demonstrates the information gap between borrowers and lenders in these markets (Baele et al, 2014), and this theory is significant in imperfect knowledge. Asymmetry information is studied by (Dignah et al, 2017) to examine information among people in economic decision-making. The participants showed that information sharing lowers adverse selection by enhancing bank-related information on credit claimants.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…As opinioned by Dignah et al (2017), the fair value accounting procedure plays a major role in the accounting standards since 1980. The initial involvement of the IAS 16 was to set accounting standards for the plant, pieces of equipment and property (Haswell, 2015).…”
Section: Fair Value Accounting Adaption and Financial Reporting Qualitymentioning
confidence: 99%